História do jornalismo em Portugal: proposta de periodização - Sousa, Jorge Pedro (2020)
Periodization systematizes and diachronically orders historical phenomena, grouping them according to common denominators and pointing out evident and verifiable continuities and ruptures in historical evolution. It is methodologically based on an interpretive intellectual exercise that starts from historical evidence, although it never fully attach to material historical reality. The present paper aimed, therefore, to propose a periodization for the history of Portuguese journalism, that never has been outlined. The following periods were defined: 1) Artisanal news press; 2) Segmentation of the press and dominance of informative artisanal press; 3) Dominance of political artisanal press; 4) Segmented pre-industrial press; 5) Segmented industrial press and development of mass daily newspapers; 6) Media segmentation of journalism, with three phases: a) Censored machines; b) Revolutionary disruption; c) Liberalization; and 7) Convergence and fusion.